2015
DOI: 10.15740/has/au/10.2/158-163
|View full text |Cite
|
Sign up to set email alerts
|

Means for retaining farming communities in semiarid regions of Gujarat state

Abstract: SUMMARY :Developmental programme are carried out to support small holder farming communities for their livelihood. The research study was conducted in Panchmahal district of Gujarat to understand the nature of agricultural system, socio-economic status, cropping and livestock rearing pattern for implementing suitable interventions. It was found that agriculture productivity was less intensive and majority of farmers had inclination towards rearing of buffaloes. Majority of the respondents did not have higher l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This had created stress on natural resources, changing lifestyle and prevalence of diseases affecting livestock. However, poor availability of quality livestock service has been a constraint (Ravikumar & Chander, 2011).Adopting low cost locally available technological alternatives may be sustainable in such smallholder system (Ravikumar et al, 2015). Thus accessing financial service and technology through such service improvise household income .…”
Section: Social Setting and Characteristics Of Rainfed Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…This had created stress on natural resources, changing lifestyle and prevalence of diseases affecting livestock. However, poor availability of quality livestock service has been a constraint (Ravikumar & Chander, 2011).Adopting low cost locally available technological alternatives may be sustainable in such smallholder system (Ravikumar et al, 2015). Thus accessing financial service and technology through such service improvise household income .…”
Section: Social Setting and Characteristics Of Rainfed Agriculturementioning
confidence: 99%
“…These institutions enable farmers to seek information and such interactions indirectly make them toinitiative driven individuals (Hansen, 2015). Ravikumar et al (2015) indicated that for improvising livelihood strategies in semiarid regions role of dairy cooperative societies need to be focussed.…”
Section: Social Support Servicementioning
confidence: 99%
“…Many developmental activities are carried out to support farming communities for their livelihood (Ravikumar et al, 2015a). Animal husbandry departments cater to health service for enhancing or sustaining productivity of livestock.…”
Section: Participation Of Community and Demonstration Of Technologiesmentioning
confidence: 99%
“…In Indian context only 5.1 percent of farming community could access information on animal husbandry (Chander et al, 2010). It was amply illustrated that under smallholder production system location specific technologies need to be considered with support of livestock owners (Ravikumar et al, 2015a;Gaikwad et al, 2015). Hence, an alternative approach is needed wherein clients should themselves assess the technology for its wider adoption.…”
Section: Assessment Of New Information Through Onfarm Experimentationmentioning
confidence: 99%
“…This is more pertinent in rain-fed areas, wherein larger variations in agro-ecological and socio-economic conditions were noticed in short distances (Vandenban and Hawkins, 1998). The type of feeding system, preference to livestock species, method of cultivation and dependence on dairy societies by smallholders in these regions needs to be given adequate attention while promoting location-specific technologies (Ravikumar et al, 2015a). It is ideal to unearth the tacit knowledge of knowledge holders for innovation promotion activities of traditional knowledge system.…”
Section: Knowledge Holder(s) and Community Being Part Of Research Systemmentioning
confidence: 99%